The Souss lagerstätte of the Anti-Atlas, Morocco: discovery of the first Cambrian fossil lagerstätte from Africa - Gerd Geyer (Nature Portfolio, 2021)
Abstract Episodic low oxygenated conditions on the sea-floor are likely responsible for exceptional preservation of animal remains in the upper Amouslek Formation (lower Cambrian, Stage 3) on the northern slope of the western Anti-Atlas, Morocco. This stratigraphic interval has yielded trilobite, brachiopod, and hyolith fossils with preserved soft parts, including some of the oldest known trilobite guts. The “Souss fossil lagerstätte” (newly proposed designation) represents the first Cambrian fossil lagerstätte in Cambrian strata known from Africa and is one of the oldest trilobite-bearing fossil lagerstätten on Earth. Inter-regional correlation of the Souss fossil lagerstätte in West Gondwana suggests its development during an interval of high eustatic levels recorded by dark shales that occur in informal upper Cambrian Series 2 in Siberia, South China, and East Gondwana.